PENYULUHAN HUKUM TENTANG PENCEGAHAN DAN PENINDAKAN KEKERASAN DALAM RUMAH TANGGA - Muh Sutri Mansyah; Hasirudin Hasri; Hayun Hayun; La Ode Muhammad Karim; Edy Nurchyo; La Ode Bunga; Zudin Zudin; Vera Merdekawati (LPPM Universitas Al Muslim, 2024)
This Community Service Activity aimed to provide knowledge and understanding about preventing and taking action against Domestic Violence in Sampuabalo Village, Buton Regency. It is hoped that this activity will be able to provide legal awareness about how to prevent and take action against domestic violence. The methods for carrying out activities were counseling, lectures and discussions. The results of the implementation of thiscommunity service activities showed that there are efforts to increase public knowledge and awareness, one of which is in the form of legal education to the Sampuabalo Village Community and the participants who attended were dominated by people who were married, and the participants looked very enthusiastic and the community even hoped for further legal education so that they could increase their knowledge about law.